Conductometric Titration of Acids in Mixed and Non-Aqueous Solutions - Нарбек Сапаевич Палванов; Ибодуллаева Мукаддас Олимбоевна; Атаджанова Замира Юсуповна; Куваниш Турсун оглы Ережепбаев (Genius Journals, 2022)
In given work happen to the results of the determination carbon acids in mixed and nonaqueous solution by method conductometry titraining acid-main. The Explored influence chemical and physical characteristic of the solvents in condition acid-main titraining. The linear dependency will Revealled between constant of acidity and value non electry permeability. The Value of the constant autoprotolys solvent also is an important factor for choice of the solvent for acid-main titraining
Keywords: Аnalysis; determination; titrimetry; conductometry